QOLP-04. THE KETOGENIC DIET PLUS STANDARD CARE FOR RECENTLY DIAGNOSED GLIOBLASTOMA: A PHASE 1 SAFETY AND FEASIBILITY TRIAL. (12th November 2021) - Hu, Jethro; Amaral, L J; Gresham, Gillian; Nelson, Thomas; Welborn, Amelia; Lockshon, Laura; Tighiouart, Mourad; Kim, Sungjin; Noorvash, Brandon; Mack, Alexandra; Rudnick, Jeremy; Phuphanich, Surasak; et al.
Abstract: INTRODUCTION: There is abundant interest in the potential therapeutic and supportive role of a ketogenic diet (KD) for glioblastoma patients. We conducted a single-arm phase 1 trial to assess the safety and feasibility of KD plus standard-of-care (SOC) in glioblastoma patients (NCT03451799). METHODS: Adults within 3 months of diagnosis participated in a 16-week intervention of a classic 3:1 KD (grams fat : grams carbohydrate + protein) with dietitian support. Blood glucose and ketone levels were assessed twice daily (Keto-Mojo), with remote monitoring of daily weight and activity (Fitbit). The primary objective was to assess safety (weight stability, CTCAE) and feasibility (maintaining ketosis > 0.3mM for > 50% of study period). Secondary objectives included assessments of progression-free survival (PFS), overall survival (OS), health-related quality of life (HRQOL), and cognition (MoCA). RESULTS: From 04/2018-02/2021, 14 patients were evaluable: female:male, 8:6, median age 55 years, KPS 80, BMI 24.5. MGMT promoter methylation: 6 present, 7 absent, 1 indeterminate. Adherence to KD was high, with all patients maintaining ketosis ( > 0.3mM) > 50% and 11 patients maintaining ketosis > 85% of study days. Adverse events (> Grade 2) potentially attributable to KD: appetite loss (Grade 2: 2); fatigue (Grade 2: 5); flu-like symptoms (Grade 2: 1); constipation (Grade 2: 5, Grade 3: 1). No patients were removed from study for safety reasons. HRQOL was stable, with improvements in role function (not statistically significant). MoCA score improved in 10/14 patients. Median PFS and OS from KD initiation were 11.7 and 29.1 months, respectively. CONCLUSION: Our findings suggest that a supervised KD plus SOC is safe and feasible in glioblastoma patients. KD was well-tolerated with encouraging trends in HRQOL and cognition. PFS and OS in this small trial compare favorably to historical control. A multicenter phase 2 trial powered to assess efficacy is planned.